PurN Is Involved in Antibiotic Tolerance and Virulence in Staphylococcus aureus - Qi Peng; Lu Guo; Yu Dong; Tingrui Bao; Huiyuan Wang; Tao Xu; Ying Zhang; Jian Han (MDPI AG, 2022)
Staphylococcus aureus can cause chronic infections which are closely related to persister formation. Purine metabolism is involved in S. aureus persister formation, and purN, encoding phosphoribosylglycinamide formyltransferase, is an important gene in the purine metabolism process. In this study, we generated a ΔpurN mutant of the S. aureus Newman strain and assessed its roles in antibiotic tolerance and virulence. The ΔpurN in the late exponential phase had a significant defect in persistence to antibiotics. Complementation of the ΔpurN restored its tolerance to different antibiotics. PurN significantly affected virulence gene expression, hemolytic ability, and biofilm formation in S. aureus. Moreover, the LD50 (3.28 × 1010 CFU/mL) of the ΔpurN for BALB/c mice was significantly higher than that of the parental strain (2.81 × 109 CFU/mL). Transcriptome analysis revealed that 58 genes that were involved in purine metabolism, alanine, aspartate, glutamate metabolism, and 2-oxocarboxylic acid metabolism, etc., were downregulated, while 24 genes involved in ABC transporter and transferase activity were upregulated in ΔpurN vs. parental strain. Protein-protein interaction network showed that there was a close relationship between PurN and GltB, and SaeRS. The study demonstrated that PurN participates in the formation of the late exponential phase S. aureus persisters via GltB and regulates its virulence by activating the SaeRS two-component system.